Streamlining robotic-assisted abdominoperineal resection - Kazunosuke Yamada; Jun Imaizumi; Ryuji Kato; Takahiro Takada; Hitoshi Ojima (World Journal of Surgical Oncology, 2023)
Abstract Background Robot-assisted surgery has proven to be a safe and feasible approach for the management of rectal cancer, including abdominoperineal resection (APR). However, it often incurs longer operative times and higher costs. This study aimed to overcome these limitations by adopting a synchronous approach utilizing an optimized team composition. Methods Data on patients who underwent robot-assisted APR at our facility between June 2022 and June 2023 were analyzed. The key points of the optimized approach included the following: At the start of the surgery, the surgeon performed an anococcygeal ligament resection from the perineal side while the bedside assistants set up the ports. Then, through console manipulation, the presacral fascia, elevated by previously placed gauze, was easily and safely incised, providing access to the perineal region. Results A total of nine patients were included in this study. The median operation time was 231 min, and the intraoperative blood loss was 170 ml. The operation time was reduced to 167.5 min, and the blood loss was 80.5 ml in cases without a trainee. Surgical site infections, classified as Clavien–Dindo grade II complications, were observed in two cases, but no obvious urinary or erectile dysfunction was observed. Conclusion The study results indicate that the challenges associated with APR can be efficiently addressed without requiring additional personnel by streamlining team composition and the synchronous approach. This optimization strategy minimizes the need for a larger surgical team, while maximizing the utilization of surgical time and resources.